Role of Women in Politics: India Scenario - Dr. Ajay Kumar Shukla (JOURNAL OF INDUSTRIAL RELATIONSHIP CORPORATE GOVERNANCE AND MANAGEMENT EXPLORER, 2023)
This paper presents the role of women in politics in Indian scenario. Indian Constitution gives equal rights to women. But women are not represented properly in politics today. Their representation in parliament and state assemblies is not satisfactory. Many social, economic and psychological factors refrain women from performing independently in politics. Generally they are accepted as widow, sister, or family member of any known politician. Women should contribute independently in the political spheres and utilize their potential. Women leadership is as successful as men leadership. If their given opportunity. Women can prove very efficient in politics. Keywords- Women, politics, empowerment, education.